Α5‐nAChR modulates melanoma growth through the Notch1 signaling pathway. Issue 11 (7th January 2020) - Dang, NingNing; Meng, Xianguang; Qin, Guojing; An, Yunhe; Zhang, QianQian; Cheng, Xiaoyan; Huang, Shuhong
Abstract: The roles of α5‐nicotinic acetylcholine receptors (α5‐nAChRs) in various types of solid cancer have been reported; however, its role in melanoma remains unknown. We knocked down α5‐nAChR expression in melanoma cells to investigate the role of α5‐nAChR in the proliferation, migration, and invasion of melanoma cells, and its effect on downstream signaling pathways. Using immunohistochemical analysis, we determined that α5‐nAChR expression is significantly increased in human melanoma tissues and cell lines compared with normal human skin tissues. Knocking down α5‐nAChR expression in melanoma cells in culture significantly inhibited the proliferation, migration, and invasiveness of melanoma cell lines. Specifically, knockdown of α5‐nAChR inhibited PI3K‐AKT and ERK1/2 signaling activity. Moreover, we confirmed that the Notch1 signaling pathway is the downstream target of α5‐nAChR in melanoma. Our findings suggest that α5‐nAChR plays a critical role in melanoma development and progression, and that targeting α5‐nAChR may be a strategy for melanoma treatment. Abstract : α5‐nicotinic acetylcholine receptors (α5‐nAChR)‐induced cell proliferation, migration, and invasion in melanoma cells. Notch1 signaling pathway inhibitor, inhibitor of mastermind recruitment‐1 (IMR‐1), bloded the effect of α5‐nAChR in melanoma cells.